2016
DOI: 10.1016/j.fcr.2016.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield, adaptation and progress in breeding for early-maturing and heat-tolerant wheat lines in South Asia

Abstract: HighlightsEach year from 2009 to 2014, 28 newly developed early-maturing high-yielding CIMMYT wheat lines were evaluated across locations in South Asia.Maximum temperatures in ME5 (continual high temperature stress regions) and minimum temperature in ME1 (terminal high temperature stress regions) had significant impact on grain yield in South Asia.Significant negative genetic correlations of grain yield with days to heading.Early maturity has the potential to improve adaptation and maintenance of genetic gains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 29 publications
9
55
0
1
Order By: Relevance
“…We also observed that GY in both the stressed environments was negatively correlated with DTHD and positively correlated with plant height, as observed previously (Mondal et al 2016). However, nursery EYT 14–15 evaluated in the DS environment was an exception to this general trend, where GY had no correlations with DTHD and plant height, because of the warmer temperatures observed in this year.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed that GY in both the stressed environments was negatively correlated with DTHD and positively correlated with plant height, as observed previously (Mondal et al 2016). However, nursery EYT 14–15 evaluated in the DS environment was an exception to this general trend, where GY had no correlations with DTHD and plant height, because of the warmer temperatures observed in this year.…”
Section: Discussionsupporting
confidence: 91%
“…This is due to the high temperatures and longer day length in this environment that are known to result in shorter cycles, quicker maturity, and accelerated crop development rates. These are considered as adaptations of plants to hot weather enabling them to avoid excessive stress (Zahedi and Jenner 2003; Fischer 2011; Semenov et al 2014; Trnka et al 2014; Mondal et al 2016). The plants in the stressed environments were also shorter than in the optimal environment (average height reduction of 15 cm, and 35.5 cm in the DS and HS environments, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Under future climatic scenarios, global climate models predict an increase in the intensity and magnitude of high-temperature episodes (Asseng et al, 2011;Lobell et al, 2012;Gourdji et al, 2012Gourdji et al, , 2013Pachauri and Meyer, 2014;Pask et al, 2014). Short episodes of high temperatures (>30°C) coinciding with a specific developmental stage or long-duration exposure to high temperatures in wheat growing regions have been reported from China, the United States, and India (Mondal et al, 2013;Tack et al, 2015;Liu et al, 2016;Mondal et al, 2016). Recently, a modeling exercise without accounting for CO 2 fertilization concluded that a 1°C increase in global temperature would lead to a decline in global wheat production ranging between 4.1 and 6.4% (Liu et al, 2016).…”
Section: Researchmentioning
confidence: 99%
“…Among these, only a few have discussed sugar beet and wheat GHG emissions [22,23]. However, only a few reports are available on wheat production; therefore, quantification of energy consumption and GHG emissions in Pakistan is very important Wheat is one of the world's major staple crops and a source of 20% of daily protein to approximately 4.5 billion people, with yearly production of 730 million tons worldwide [24,25]. In Pakistan, wheat is a chief staple food and it dominates all crops in acreage (8740 thousand hectares) and production (25,195 thousand tons), throughout the country ( Figure 1) and also contributes 1.6% and 8.9% to the country's GDP and value-added agriculture, respectively [26].…”
Section: Introductionmentioning
confidence: 99%